2016
DOI: 10.2298/sta1666173k
|View full text |Cite
|
Sign up to set email alerts
|

New evidence for prehistoric copper metallurgy in the vicinity of Bor

Abstract: The last three years of archaeological investigations at the site Ru`ana in Banjsko Polje, in the immediate vicinity of Bor, have provided new evidence regarding the role of non-ferrous metallurgy in the economy of the prehistoric communities of north-eastern Serbia. The remains of metallurgical furnaces and a large amount of metallic slags at two neighbouring sites in the mentioned settlement reveal that locations with many installations for the thermal processing of copper ore existed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Turning to the nearby site of Ružana, excavators again found that most of the slags, including large pieces (up to 1.7 kg), were mixed within the accumulation of other finds (pottery, animal bones), but in contrast to Trnjane, there was evidence of smelting with recovery of a burned amorphous structure accompanied by a smaller dump pit (Kapuran et al, 2016), although sadly the limited area of excavation prevented further investigation. Evidence of smelting was also found at the third site of Čoka Njica, during excavations in 2019, which revealed an oval shaped feature (100 × 80 cm) with remains of curved clay wall, Crucial for the cultural and chronological determination of the copper producing sites in Eastern Serbia are pottery finds and recently obtained radiocarbon dates (Kapuran et al, , 2014(Kapuran et al, , 2020.…”
Section: The Archaeological Background -The Smelting Sites Trnjane Ru...mentioning
confidence: 99%
See 1 more Smart Citation
“…Turning to the nearby site of Ružana, excavators again found that most of the slags, including large pieces (up to 1.7 kg), were mixed within the accumulation of other finds (pottery, animal bones), but in contrast to Trnjane, there was evidence of smelting with recovery of a burned amorphous structure accompanied by a smaller dump pit (Kapuran et al, 2016), although sadly the limited area of excavation prevented further investigation. Evidence of smelting was also found at the third site of Čoka Njica, during excavations in 2019, which revealed an oval shaped feature (100 × 80 cm) with remains of curved clay wall, Crucial for the cultural and chronological determination of the copper producing sites in Eastern Serbia are pottery finds and recently obtained radiocarbon dates (Kapuran et al, , 2014(Kapuran et al, , 2020.…”
Section: The Archaeological Background -The Smelting Sites Trnjane Ru...mentioning
confidence: 99%
“…Further indications of Bronze Age copper smelting activity were discovered in a small-scale excavation at the site of Ružana, just about 1.5 km to the southeast of Trnjane Kapuran et al, 2016), whilst unambiguous traces of copper smelting have also been attested at the site Čoka Njica, located approximately 3 km further east of Trnjane and Ružana. Finds of slags and Bronze Age pottery are also known from a number of other sites in the surrounding area, yet there is still a lack of tangible evidence in terms of chronology.…”
Section: Introductionmentioning
confidence: 96%
“…73 Other close analogies can be find in the nearby sites of Ružana 1 and 2. 74 Assigned to the bowls is also one wall fragment with incised ornaments typical of the Early Bronze Age Verbicioara culture in neigh bouring Oltenia. 75…”
Section: Bowlsmentioning
confidence: 99%
“…99 An absolute date from this site positions the settlement into the final quarter of the 6 th millennium calBC. 100 Plates with a thickened rim have also been recorded within the Gumnište II horizon in Pavlovac, together with globular vessels characteristic for the Vinča-Tordoš II phase, which remained in use within the younger Gumnište III hori zon, together with slightly biconical bowls and cari nated bowls. 101 All of the absolute dates indicate that the plates with a thickened rim, bowls with a carinated form and vessels on a hollow foot were common for the Vinča culture within the socalled Mountainous Region of the Central Balkans during the final quarter of the 6 th millennium calBC, which corresponds to the Vinča-Tordoš II phase, according to M. Garašanin and Vinča B phase, according to V. Milojčić.…”
Section: The Eastern and Western Zones Of The Mountainous Regionmentioning
confidence: 96%